PENGARUH LAYANAN DIGITAL PERBANKAN,TINGKAT KOMPETISI, DAN EFISIENSI TERHADAP PROFITABILITAS PERBANKAN - Ayu Panrita Ramadhanty (Contemporary Studies in Economic, Finance and Banking, 2023)
This study aims to find out how mobile banking, internet banking, the level of competition, and efficiency affect banking profitability based on the fluctuation of ROA in 2015-2021 and the increase in the number of digital banking service transactions in 205-2021. This study uses panel data regression to see the effect of the independent variables on the dependent variable. The dependent variable in this study is Return on Assets (ROA), with independent variables Mobile Banking (X1), Internet Banking (X2), Competition (X3) which is proxied by the Lerner index, and Efficiency (X4). This research shows that there is a positive impact on Competition (X3) and a negative impact on Efficiency (X4) on ROA (Y), and the Mobile Banking (X1) and Internet Banking (X2) variables have no impact on ROA(Y).